Effect of Dietary Inclusion of Turmeric (Curcuma longa) and Garlic (Allium sativum) Powders as Feed additives on Performance of Broiler Chicken - Chowdhary, Sonali (Indian Journal of Animal Nutrition, 2021)
The present study was conducted to evaluate the effect of dietary inclusion of garlic, turmeric and their combinations on performance of broilers (Cobb strain). Two hundred and forty day-old unsexed broiler chicks were procured and randomly divided into five dietary treatment group (n=48). Birds in control (C) group were administered antibiotic levofloxacin at 2.5 g/l of drinking water, however, antibiotic was replaced with dietary inclusion of either 1% turmeric (T1), 1% garlic (T2), 0.6% turmeric+0.4% garlic (T3), or 0.6% garlic+0.4% turmeric (T4). The diets formulated were isocaloric and isonitrogenous. The feeding trial was conducted for 6 weeks. The results revealed significantly (P0.05) among groups. Feed conversion ratio was found to be better in groups T2 and T4. Protein efficiency ratio was found to be higher in group T2 (P